Особливості вирощування молодняку телят - Лисенко, М. Ю.; Lysenko, N. Y.; Карлова, Ліна Валентинівна; Karlova, L. V.; Karlova, L.; Karlova, Lina V.; Karlova, Lina Valentinovna; Karlova, Lina Valentunivna; Karlova, Lina (Дніпровський ДАЕУ, 2021)
Наведено результати досліджень вирощування молодняку телят української червоної молочної породи за додавання до їх основного раціону L-метионіну в кількості 3,0 г на 1 голову за добу. Встановлено, що телята 2 (дослідної групи), які споживалиL-метионін витрачали на 0,26 корм. од. (6,3 %) менше корму. У них відмічено зростання середньодобових приростів живої маси за період досліду 121,1 г (15,3 %). The results of research on the rearing of young calves of the Ukrainian red dairy breed with the addition of L-methionine in the amount of 3.0 g per 1 head per day to their main diet are presented. It was found that calves 2 (experimental group) who consumed L-methionine consumed 0.26 feed. from (6,3 %) less feed. They showed an increase in the average daily gain of live weight during the experiment 121.1 g (15,3 %).
Features of breeding of young calves
Карлова Ліна Валентинівна https://orcid.org/0000-0001-8213-8588
Keywords: витрати корму; feed costs; телята; calves; L-метионін; L-methionine; жива маса; live weight; середньодобовий приріст; average daily gain